Identification and mapping of QTLs and their corresponding candidate genes controlling high night‐time temperature stress tolerance in wheat (Triticum aestivum L.) - Kaviraj S. Kahlon; Kanwardeep S. Rawale; Sachin Kumar; Kulvinder S. Gill (The Plant Genome)
Abstract With every 1°C rise in temperature, yields are predicted to decrease by 5%–6% for both cool and warm season crops, threatening food production, which should double by 2050 to meet the global demand. While high night‐time temperature (HNT) stress is expected to increase due to climate change, limited information is available on the genetic control of the trait, especially in wheat (Triticum aestivum L.). To identify genes controlling the HNT trait, we evaluated a doubled haploid (DH) population developed from a cross between an HNT tolerant line KSG1203 and KSG0057, a selection out of a mega variety PBW343 from South East Asia that turned out to be HNT susceptible. The population, along with the parents, were evaluated under 30°C night‐time (HNT stress) keeping the daytime temperature to normal 22°C. The same daytime and 16°C night‐time temperature were used as a control. The HNT treatment negatively impacted all agronomic traits under evaluation, with a percentage reduction of 0.5%–35% for the tolerant parent, 8%–75% for the susceptible parent, and 8%–50% for the DH population. Performed using sequencing‐based genotyping, quantitative trait locus (QTL) mapping identified 19 QTLs on 13 wheat chromosomes explaining 9.72%–28.81% of cumulative phenotypic variance for HNT stress tolerance, along with 13 that were for traits under normal growing conditions. The size of QTL intervals ranged between 0.021 and 97.48 Mb, with the number of genes ranging between 2 and 867. A candidate gene analysis for the smallest six QTL intervals identified eight putative candidates for night‐time heat stress tolerance.